The dispersion of clonally related cells in the developing chick telencephalon. - Szele, F; Cepko, C (1998)
Lineage analysis in the chick telencephalon was carried out using a library of retroviral vectors. Clones were analyzed in posthatch day 14-21 animals for the phenotype and final locations of sibling cells. Clones often contained multiple types of neurons and glia. Clones of more than four cells almost always crossed functional boundaries. They were dispersed primarily along the rostrocaudal axis or in multiple directions, e.g., along the rostrocaudal and mediolateral axes. In order to begin to understand how the final patterns of dispersion were reached, embryonic tissue was examined. Radial migration, apparently supported by radial glial cells, occurred within the proliferative zones in all clones. In contrast to the migration of cells in the mammalian telencephalon, no tangential migration within the proliferative zones was observed at any age examined. However, beginning at embryonic day 4.5, tangential migration in the mantle zone in multiple directions was observed among the majority of clones. This type of migration occurred as soon as a mantle zone became apparent. It appeared that the tangential migration was not along radial glial processes. As in the mammalian telencephalon and chick diencephalon, dispersion among clonally related cells in the chick telencephalon is frequent, is extensive, and results from tangential migration in a variety of directions.